Stability of tibial defect reconstruction with fibular graft and unilateral external fixation: a finite element study - Chen, Huiqiang (e-Century Publishing Corporation, 2014)
Tibial defect is generally caused by high-energy injury, tumor, osteomyelitis, development deformity and bone non-union after internal fixation. This study was to determine stability of tibial defect reconstruction with fibular graft (FG) of different lengths by single free vascularized fibular graft (SFVFG) and double-barrel free vascularized fibular graft (DBFVFG). The left lower extremity of a male volunteer was scanned with computer tomography scanner. The contours of the tibia and fibula were extracted and the geometry of both bones rebuilt. From this intact model, the models of tibial defect reconstruction with fibular graft and external fixation were developed. Inter-fragmentary motion (IFM) and Von Mises stress on the fibular bone flap, and the locations of maximum Von Mises stress were introduced to quantify the biomechanical environment. Under the condition of the same graft length, the Von Mises stress value in DBFVFG group was 1.37 to 1.77 times higher than that in SFVFG group. When the length of graft was greater than 15 cm in the SFVFG group, the IFM exceeded 1 mm, but the IFM of the graft in the DBFVFG group was always less than 1 mm. The maximum Von Mises stress of models was frequently located at the second or third pin-bone interface. Thus, external fixation can provide a stable biomechanical environment for the reconstruction of tibial defect by both SFVFG and DBFVFG. The second or third pin-bone interface requires intensive care and that in the reconstruction of tibial defect by SFVFG, the graft length should not exceed 15 cm.